Hepatic Δ9, Δ6, and Δ5 desaturations in non-insulin-dependent diabetes mellitus eSS rats - Montanaro, Mauro Aldo (2003)
Both diabetes mellitus type 1 and diabetes mellitus type 2 are widespread diseases that alter carbohydrate and lipid metabolism. e Stilmann-Salgado (eSS) rats are experimental animals that spontaneously evolve to a state similar to that of young people affected by non-insulin-dependent diabetes mellitus (NIDDM; type 2). Using 6-mon-old eSS rats that, according to the literature [Martinez, S.M., Tarres, M.C., Montenegro, S., Milo, R., Picena, J.C., Figueroa, N., and Rabasa, S.R. (1988) Spontaneous Diabetes in eSS Rats, Acta Diabetol. Lat. 25, 303-313], had already developed insulin resistance, we investigated the changes evoked on delta9, delta6, and delta5 liver desaturases. The abundance of mRNA and enzymatic activities were measured, as well as the FA composition of liver microsomal lipids. Compared to control rats, the mRNA content and activity of SCD-1 (stearoyl CoA-desaturase, isoform of the delta9 desaturase) were significantly higher, whereas the mRNA and activities of delta6 and delta5 desaturases were not significantly modified. Correspondingly, the proportion of 18:1n-9 and the ratios of 18:1n-9/18:0 and 16:1/16:0 in lipids were significantly increased, whereas the proportion of 20:4n-6 was unaltered. These effects were found while glycemia was constant or increased. The results are completely opposite those described in insulin-dependent diabetes mellitus (type 1), in which a depression of all the desaturases is found. They suggest that in eSS rats, the activities of the desaturases were not modified by an insulin-resistance effect. Moreover, we suggest that the enhancement of SCD-1 activity might be considered as another typical sign of the NIDDM syndrome, because it has also been found in other animal models of NIDDM, for example, the ones evoked by the sucrose-rich diet and in the Zucker rat.